Clinical and economic burden of anxiety/depression among older adult COPD patients: evidence from the COPD-AD China Registry study - Zhao, Xuanna; Liu, Gege; Liu, Dewei; Zou, Li; Huang, Qiu; Chen, Min; Li, Dongming; Wu, Bin; Wu, Hua; Huang, Dan; Wu, Dong (Frontiers in Psychiatry, 2024)
Background: Anxiety and depression are common in patients with chronic obstructive pulmonary disease (COPD), especially elderly patients. This can complicate the disease progression and lead to increased clinical and economic burden. We sought to investigate the clinical and economic burdens associated with the presence of anxious and/or depressive symptoms among elderly COPD patients.We screened 579 patients aged over 60 years and diagnosed with COPD via a lung function test following the 2017 Global Initiative Chronic Obstructive Lung Disease (GOLD) guidelines. Anxiety and depression were measured using the Hospital Anxiety and Depression Scale (HADS) through face-to-face interviews at admission. Follow-up was conducted by telephone calls at 6, 12, 18, 24, and 36 months after discharge to assess clinical and economic burden. COPD-anxiety and/or depression patients were matched to patients without anxiety and depression (COPD-only) using propensity scores. Multivariate regression models were used to compare clinical and economic burden between COPD-anxiety and/or depression and COPD-only groups.Results: Compared with COPD-only patients, COPD patients complicated with anxiety and/or depression had increased clinical burden, including higher COPD-related 2 / 18 outpatient visits, COPD-related hospitalizations, and length of COPD-related hospitalizations (p<0.001). Moreover, they also had an increased economic burden, including higher annual total healthcare costs, medical costs, and pharmacy costs (p<0.001).Elderly COPD patients with anxiety or depression had significantly higher clinical and economic burdens than patients without these comorbidities. These findings deserve further exploration and may be useful for the formulation of relevant healthcare policies.